Extinct Monsters to Deep Time : conflict, compromise, and the making of Smithsonian's fossil halls - Marsh, Diana E., 1986- (Museums and collections, 2019)
Extinct Monsters to Deep Time is an ethnography that documents the growing friction between the research and outreach functions of the museum in the 21st century. Marsh describes participant observation and historical research at the Smithsonian's National Museum of Natural History as it prepared for its largest-ever exhibit renovation, Deep Time.' As a museum ethnography, the book provides a grounded perspective on the inner-workings of the world's largest natural history museum and the social processes of communicating science to the public.